"Land imaginaries" in Western Canada: (financial) neoliberalism, agrarianism, and the contemporary politics of agricultural land. (June 2023) - Beingessner, Naomi; Magnan, André; Wendimu, Mengistu
This article examines contemporary political controversies over agricultural land in the prairie region of Canada. We suggest that contemporary land politics reflect elements of continuity and change in a distinctive "land imaginary" connected to the region's history and recent restructuring. While neoliberalism, and more recently, financialization, have been the main drivers of restructuring in recent decades, certain strands of agrarianism continue to shape social relations in the agricultural sector. We present three case studies, the first of which examines the controversy over institutional investment in farmland, focusing on the Canada Pension Plan's large-scale purchase of Saskatchewan land. The second case study examines conflicts over the deregulation of government-run community pastures, with implications for the ranching sector, environmental conservation, and the future of native prairie. Our third case study focuses on the proposed sale and land-use conversion of government-owned pasture land in Alberta, dubbed "Potatogate". We examine the role of farmers, ranchers, governments, NGOs, and private interests in shaping debates over land ownership and use. We argue that these conflicts reveal a tension between (financial) neoliberalism and agrarian arguments and values, with significant differences across agricultural sub-sectors.